Sistem Perekonomian Terbuka - Muhammad Haikal Muqowwi; Zakhi Mubarok; Rizqi Putri Solina; Muhammad Taufiq Abadi (JOURNAL SAINS STUDENT RESEARCH, 2024)
Every country has the same goal, namely achieving a high level of prosperity for its country. Nowadays, one of the important conditions for achieving prosperity is globalization, making a country's economic system develop in a more open direction, both in the economic and financial fields. Indonesia is a country with an open economic system. Whatever happens to the global economy, the impact will be felt in the national economy. An open economic system provides opportunities for its people to interact in the economic sector with other countries, whether individuals, the private sector or government, where economic activities can take the form of trade in goods and services, exchange of technology and so on. the relationship between the value of other imports made and the level of community income and national income achieved. As has been stated, imports are affected expenditure, which means that the higher the national income, the higher the imports.